Functional responsibility of international organizations : the European Union and international economic law - Leinarte, Emilija (Cambridge : Cambridge University Press, 2021)
This book provides a novel approach to the allocation of international responsibility in a multilayered structure like the European Union. Introducing a new concept of functional international responsibility, this study finds that in international economic law the focus of international dispute settlement bodies is not on the responsible party, but on a party best placed to bear responsibility. The book offers a comprehensive analysis of international rules of responsibility and international dispute settlement practice, primarily that of the World Trade Organization and investment arbitration. The study offers a practically applicable approach to questions of international responsibility which will assist international adjudicators, EU and Member States' officials and third country government agents who negotiate economic agreements and are involved in international economic disputes. The book is also relevant to those interested in the governance and accountability questions under the new EU-UK Trade and Cooperation Agreement.
The governing law -- Independent responsibility of the EU and its member states -- The concept of an organ and agent of the EU -- The nature of remedies in international economic law -- Identification of the proper respondents -- The optimal respondent -- Multiple respondents in WTO dispute-settlement -- Normative implications for the EU's free trade agreements.
Title from publisher's bibliographic system (viewed on 09 Dec 2021).
Keywords: European Union; World Trade Organization -- European Union countries; Court of Justice of the European Union; International agencies; Foreign trade regulation -- European Union countries; International agencies -- European Union countries